Reactualization of KH. Yusuf Hasyim's Educational Values as a Response to Moral Decadence in the Context of Salaf Education at the Tebuireng Islamic Boarding School - Kumalasari, Andani; Syafi’ie, Musta’in (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This article explores the revitalization of KH. Yusuf Hasyim’s educational values as a response to the moral decline among the younger generation, emphasizing their application within the educational framework of the Tebuireng Salaf Islamic boarding school. Employing a descriptive qualitative method, the study draws on literature reviews and in-depth interviews with both current students and alumni of the pesantren. The findings reveal that KH. Yusuf Hasyim’s core educational principles such as sincerity, exemplary conduct, discipline, social responsibility, and the integration of religious and modern sciences remain relevant and effective in cultivating students with noble character, intellectual openness, and resilience in facing contemporary challenges. The process of revitalization involves adapting teaching strategies, reinforcing a values-oriented curriculum, and fostering an environment supportive of moral development. These results affirm that value-based education in traditional Islamic boarding schools offers a practical approach to addressing the moral crisis in the era of globalization.